Fundamentals of database systems - Elmasri, Ramez (Addison Wesley, 2007)
Clear explanations of theory and design, broad coverage of models and real systems, and an up-to-date introduction to modern database technologies result in a leading introduction to database systems. With fresh new problems and a new lab manual, students get more opportunities to practice the fundamentals of design and implementation. More real-world examples serve as engaging, practical illustrations of database concepts. The Fifth Edition maintains its coverage of the most popular database topics, including SQL, security, data mining, and contains a new chapter on web script programming for databases.